Pewarnaan Alternatif dengan Menggunakan Filtrat Kulit Kenari pada Uji Mikroskopik Jamur Candida Albicans dan Aspergillus Niger - Erpi Nurdin (Fakultas MIPA UNM, 2022)
Abstract. Walnut is a native plant of Indonesia that grows a lot in eastern Indonesia, such as North Sulawesi, Maluku and the island of Seram. Walnut shells contain phenolic compounds which are natural antioxidants. Phenolic compounds are used as preservatives because phenol can scavenge free radicals. The color contained by walnut shells may be an alternative to fungal microscopic test staining. This study aims to see the fungus on alternative coloring of walnut shells by using a microscopic test. The method used in this research is descriptive with an experimental approach. The results of the study identified as many as 3 samples (100%) Candida albicans and 3 samples (100%) Aspergillus niger in the filtrate by heating treatment, as well as 3 samples (100%) Candida albicans and 3 samples (100%) Aspergillus niger in the filtrate with treatment without heating. Microscopic observations of Candida albicans and Aspergillus niger fungi, appeared more clearly and stained with the use of alternative coloring filtrate of walnut shell filtrate with the heating process. Conclusion : Alternative staining with walnut shell filtrate can be used to color Candida albicans and Aspergillus niger fungi. The filtrate by heating is more effective in the microscopic examination of fungi. Keywords: walnut shell, alternative coloring, candida albicans, aspergillus niger